2009
DOI: 10.1063/1.3268466
|View full text |Cite
|
Sign up to set email alerts
|

Structural properties of wurtzitelike ScGaN films grown by NH3-molecular beam epitaxy

Abstract: Scandium gallium nitride (ScxGa1−xN) alloy films with low Sc concentrations (up to approximately x=0.08) were grown using molecular beam epitaxy with NH3 as a reactive N source, on GaN films that were grown on sapphire using metalorganic vapor phase epitaxy (MOVPE). High-resolution x-ray diffraction and transmission electron microscopy revealed that both the c and the a lattice parameters increased with increasing Sc concentration, as predicted for a wurtzite-structure alloy. As the Sc content increased, the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 26 publications
4
20
0
Order By: Relevance
“…[6][7][8] Although ScN is stable in the rocksalt structure (a ¼ 4.5045 6 0.0005 Å ), 9 Sc x Ga 1Àx N alloys are expected to remain stable in the wurtzite (WZ) structure with direct band gaps up to x % 0.27, 5 when strained to GaN. Epitaxial films of Sc x Ga 1Àx N have already been achieved 10,11 in which Sc substitutes directly for Ga, accompanied by a small local distortion (increase in u) around the Sc atom. 12 However, defects such as dislocations and stacking faults are known to affect the lifetimes and efficiencies of III-nitride devices strongly.…”
mentioning
confidence: 98%
“…[6][7][8] Although ScN is stable in the rocksalt structure (a ¼ 4.5045 6 0.0005 Å ), 9 Sc x Ga 1Àx N alloys are expected to remain stable in the wurtzite (WZ) structure with direct band gaps up to x % 0.27, 5 when strained to GaN. Epitaxial films of Sc x Ga 1Àx N have already been achieved 10,11 in which Sc substitutes directly for Ga, accompanied by a small local distortion (increase in u) around the Sc atom. 12 However, defects such as dislocations and stacking faults are known to affect the lifetimes and efficiencies of III-nitride devices strongly.…”
mentioning
confidence: 98%
“…Rejection of the harmonics was achieved via a Si-coated mirror run at 3.5 mrad glancing angle and the focusing was obtained with two adaptive Si-coated mirrors (bimorph piezoelectric systems) run in the Kirkpatrick-Baez geometry. At the Sc K-edge (4488.6 eV), this configuration permits an incident beam of horizontal width ~600 µm and vertical height ~50 µm to be obtained on the sample, with a flux of ~10 13 photons/s and an energy resolution of 0.64 eV FWHM. The fluorescence emitted by the sample was monochromatised with a Johann-type spectrometer equipped with five analysers and run in the vertical Rowland geometry at a scattering angle of 90° [16].…”
Section: Experimental Techniquesmentioning
confidence: 99%
“…The GaN-onsapphire pseudo-substrate was grown using metalorganic vapour phase epitaxy (MOVPE) [12]. Details of the Sc x Ga 1-x N growth conditions have been reported previously [9] [13]. HRXRD was performed using a Panalytical X-Pert Pro MRD machine in the triple-axis configuration using a four-bounce asymmetric Ge(220) monochromator and a triple-bounce analyser.…”
Section: Experimental Techniquesmentioning
confidence: 99%
“…All studies have predicted that Sc x Ga 1-x N alloys will be metastable with respect to rock-salt structure ScN and wurtzite-structure GaN. However, in practice Sc x Ga 1-x N alloys can be grown in epitaxial thin film form under a range of growth conditions [13][14][15] . Recent high-quality calculations also concluded that (0001)-oriented Sc x Ga 1-x N films can be stabilised using inplane compressive epitaxial strain (e.g.…”
mentioning
confidence: 99%